Combination of pyrrole and pyridine for constructing selective and sensitive Zn2+ probes. (May 2017) - Wei, Xiaodong; Wang, Qing; Tang, Weiqiang; Zhao, Shuangliang; Xie, Yongshu
Abstract: The selective and sensitive detection of zinc ions has been an important research topic because of the vital role played by zinc ions in numerous physiological activities, and fluorescent probes have emerged as effective and powerful tools for zinc detection because of their simplicity andcereal-time monitoring nature. In this work, with the purpose to improve the binding affinities and sensitivities of dipyrrin based fluorescent Zn 2+ probes, strongly coordinating pyridyl moieties were introduced into dipyrrins. Aroylation of 5-pentafluorophenyl and 5-unsubstituted dipyrromethanes with picolinoyl chloride afforded two corresponding dipicolinoyl dipyrromethanes, which were further oxidized with 2, 3-dichloro-5, 6-dicyano-1, 4-benzoquinone (DDQ) to afford the expected 5-pentafluorophenyl-substituted dipicolinoyl dipyrrin and a unique unexpected dipicolinoyl dipyrrolyl ketone, respectively. Both of these compounds exhibited noticeable fluorescence "turn-on" responses specifically to Zn 2+ over other metal cations, with fluorescence enhancements of 87 fold and 119 fold, respectively. However, because of the different substituents at the 5 positions and the different conjugation frameworks, distinct Zn 2+ sensing behavior was observed. For the 5-pentafluorophenyl-substituted dipicolinoyl dipyrrin, the sensing of Zn 2+ induced a color change from light orange to pink accompanied with enhanced red fluorescence. Whereas, the sensing of Zn 2+ by the dipicolinoyl dipyrrolyl ketone induced the color change from nearly colorless to bright yellow and enhanced green fluorescence. Based on high binding affinities and the dramatic spectral responses, both of the probes exhibit high sensitivities towards Zn 2+ with detection limits of 9.8 nM and 6.3 nM, respectively. In addition, fast responses within 10 s and wide applicable pH ranges are indicative of their potential applications as promising zinc probes. Finally, the 5-pentafluorophenyl dipicolinoyl dipyrrin was successfully applied to cell imaging in Hela cells, demonstrating its practical applicability. It is noteworthy that the single crystal structure of a Zn 2+ complex of the dipicolinoyl dipyrrolyl ketone was successfully analyzed by X-ray diffraction, which revealed an interesting tetranuclear Zn 2+ coordination structure. These results provide further insights into the design of highly sensitive Zn 2+ probes by introducing pyridyl moieties into dipyrrin platforms. Graphical abstract: Highlights: Strongly coordinating pyridyl moieties introduced to dipyrrin platforms. Distinct Zn 2+ sensing behavior modulated by different substituents. Impressive detection limits of 9.8 and 6.3 nM. Crystal structure of an interesting tetranuclear Zn 2+ complex.